Dietary probiotic Pediococcus acidilactici MA18/5M modulates the intestinal microbiota and stimulates intestinal immunity in rainbow trout (Oncorhynchus mykiss). Issue 6 (18th August 2019) - Al‐Hisnawi, Ali; Rodiles, Ana; Rawling, Mark D.; Castex, Mathieu; Waines, Paul; Gioacchini, Georgia; Carnevali, Oliana; Merrifield, Daniel L.
Abstract: A study was conducted to evaluate the probiotic effect of Pediococcus acidilactici MA18/5M on rainbow trout, Oncorhynchus mykiss . Fish (310 ± 9 g) were fed a control diet or a P. acidilactici ‐supplemented diet (at 2.4 × 10 6 CFU/g) for 4 weeks. The probiotic was observed to populate the intestine with levels ranging from log 3.7 to 5.4 CFU/g. Furthermore, these populations were able to persist for at least 24 hr after the cessation of probiotic feeding. High‐throughput sequencing analysis of bacterial 16S rRNA libraries demonstrated that P. acidilactici was able to modulate the gut microbiome of rainbow trout and that the probiotic was detected as a common taxon on the mucosa and in the digesta of the probiotic fish ( p < .05). Real‐time polymerase chain reaction demonstrated that feeding the probiotic upregulated pro‐inflammatory cytokines, interleukin‐1β, and interleukin‐8 and downregulated anti‐inflammatory interleukin‐10 compared to the control‐fed fish. Furthermore, the mRNA levels for the mucosal antibody immunoglobulin T was also elevated in probiotic‐fed fish. These findings help to explain some of the mechanisms behind the previously reported observed benefits of using this probiotic in the intestinal morphology and immunity of rainbow trout.